THE LOGIC OF RELIGIOUS AND THEOLOGICAL LANGUAGE - Macquarrie, John (Journal of Dharma, 1992)
Twenty-five years ago, I published a book with the title GodTalk, l and with the explanatory subtitle ’ ’An Examination of the Language and Logic of Theology". At that time the question about religious language was very different from what it is today. In 1967 we were still in the period when analytical philosophy and even logical positivism were very strong, and when many philosophers, especially in the English-speaking countries, were following in the paths of A. J. Ayer and maintaining that language about God is meaningless, or, at most. simply an expression of emotion. That very negative point of view, which seemed to offer a shortcut to the end of religious argument, has in the meanwhile died the death of a thousand qualifications. Already in the nineteen-sixties people were doubting whether one could really equate the meaning of a pro. position with the method of its verification. Jonathan Cohen pointed out that it is not really so clever to complain that someone’s remarks are meaningless, for there are many kinds of meaning besides the kind that Ayer and company had talked about. 2 So then the complaint was that religious language, though not meaningless, is incoherent. But again philosophers came along who showed that a very good case can be made for the coherence of religious and theological language. The ground of criticism shifted again, and in effect we were back to the situation that had obtained before the days of logical positivism — a situation in which there is an unfinished and perhaps inconclusive argument between theists and atheists, but one in which neither side can be dismissed as using meaningless language, and each is called to new exertions and refinements of argument. It is now clear that language is, to use an expression introduced, I think, by Robert Evans,4 multidimensional - it has more